(untitled) (Confluenţe Bibliologice, 2021)
The article presents the collection of volumes published between 1921-1945, dedicated to the popularization of agricultural knowledge, being patronized by the "Society of Agronomists" in Romania, edited by: D. G .Chițoiu, V. Georgescu and G. I. Savin. This Calendar has an encyclopedic character, it deals with historical issues, the chronicle of events, religious anniversaries on days and months, national holidays, the existence of colonies on the Dobrogea territories, it keeps track of cattle fairs, postal tariffs and official train fares.